Fog in heterogeneous environments: the relative importance of local and non‐local processes on radiative‐advective fog formation. (8th April 2020) - Ducongé, L.; Lac, C.; Vié, B.; Bergot, T.; Price, J. D.
Abstract: A 100 m resolution simulation of radiation fog observed during the Local And Non‐local Fog EXperiment (LANFEX) was performed over the Shropshire hills (UK) in order to understand the impact of local circulation on valley fog formation. The model correctly resolves all valleys and their different geometries, their associated dynamical features, and the different fog conditions between the measurement sites. Passage of stratocumulus during the night led to fog dissipation and gave the opportunity to study two fog formation stages. In the narrow valleys, fog formed at the valley floor and non‐local drainage‐flow processes acted to dissipate it. This equilibrium determined the fog optical thickness, which varied within and between valleys. Wider basins were more subject to dense fog conditions (due to local formation) than narrower valleys, where advecting fog events are locally observed through basins overflowing. The largest and most open valley of Jay Barns was impacted by numerous circulations from narrower tributary valleys, and their complex interactions affected fog formation differently between events. The impact of cloud microphysics on the simulated fog is studied by comparing simulations with one‐moment and two‐moment schemes. The use of a two‐moment scheme brings improvements when the prognostic number concentration is used to compute cloud optical properties, meaning that the radiative impact of droplet concentration is greater than its gravitational settling effect. Abstract : During IOP 12 of the LANFEX campaign in Shropshire (UK), the largest valley was subject to dense fog conditions due to positive contributions from local (condensation) and non‐local (advection) processes. In narrow valleys, the local formation was partially offset by non‐local destruction within drainage flows. In the narrowest valley, advecting fog was even locally observed through fog overflowing from an upstream basin when drainage flow increased at a valley lateral constriction. The figure shows integrated cloud water content between the surface and 150 m height (g·m −2 ) at 0130 UTC on 2 October 2015. Arrows show the averaged horizontal wind between 5 and 50 m above ground within the valley. Black circles show the main sites of LANFEX and the table summarises the main processes driving fog formation at each site (local for condensation/evaporation, non‐local for advection).